Energy Harvesting System Design for Converting Noise into Electrical Energy - Hamid Akbar, Fitria Hidayanti, Erna Kusuma Wati (International Journal of Advanced Science and Technology, 2020)
This research aims to convert noise becomes electrical energy using an energy harvesting system. The noise around us is a form of wasted energy. The sound (acoustic) energy can be utilized to produce electrical energy. In this study conducted a test using generator function with a variation of frequency and result obtained in simulation and then compared to result. The research used loudspeaker conversion used manifold buzzer piezoelectric ceramic treble rectangle audio speakers with a size of 8.6 cm x 8.6 cm x 7.2 cm as a conversion to the energy harvester system. Test results using the sound source of the function generator at a frequency of 60 – 80 Hz. The highest response occurred at a frequency of 69 Hz with a voltage value of 3.2 Volt, current 3.2 mA and power 10.24 milliwatt in and testing with a variation in frequency 60 – 500 Hz response highest occurred at a frequency of 70 Hz with a voltage value of 1.68 Volt, current 1.68 mA and power 2.8224 milliwatt. The maximum sound pressure level in this study was 90 dB. The output voltage of the converting loudspeaker is measured at 1 kΩ resistor. Research the two sound sources using subwoofer speakers. The maximum sound pressure level in this study was 103 dB. The output voltage of the converting loudspeaker is measured at 100 Ω resistor. Results of experiments on the converting loudspeaker result in an electrical voltage of 5.56 volt for 10 hours.